T cell Tolerance in Early Life - Yang, Lijun; Jin, Rong; Lu, Dan; Ge, Qing (Frontiers in Immunology, 2020)
T cell-mediated immune tolerance is a state of unresponsiveness of T cells towards specific self or non-self antigens. This is particularly essential during prenatal/neonatal period when T cells are exposed to dramatically changing environment and required to avoid rejection of maternal antigens, limit autoimmune responses, tolerate inert environmental and food antigens and antigens from non-harmful commensal microorganisms, promote maturation of mucosal barrier function, yet mount an appropriate response to pathogenic microorganisms. The cell-intrinsic and cell extrinsic mechanisms promote the generation of prenatal/neonatal T cells with distinct features to meet the complex and dynamic need of tolerance during this period. Reduced exposure or impaired tolerance in early life may have significant impact on allergic or autoimmune diseases in adult life. The uniqueness of conventional and regulatory T cells in human umbilical cord blood (UCB) may also provide certain advantages in UCB transplantation for hematological disorders.